Effects of the Integrated Behavioral Health Project's Efforts to Promote Integrated Care Under Funding from the California Mental Health Services Authority - Cerully, Jennifer L. (RAND Corporation, 2015)
Describes the methods and results of a RAND evaluation of the Integrated Behavioral Health Project's efforts to promote the integration of mental and physical health care among various health care stakeholders in California.